Difference between revisions of "2007 USAMO Problems/Problem 5"

m
(Solutions)
 
Line 5: Line 5:
  
 
=== Solution 1 ===
 
=== Solution 1 ===
We proceed by induction.
+
The proof is by induction. The base is provided by the <math>n = 0</math> case, where <math>7^{7^0} + 1 = 7^1 + 1 = 2^3</math>. To prove the inductive step, it suffices to show that if <math>x = 7^{2m - 1}</math> for some positive integer <math>m</math> then <math>(x^7 + 1)/(x + 1)</math> is composite. As a consequence, <math>x^7 + 1</math> has at least two more prime factors than does <math>x + 1</math>. To confirm that <math>(x^7 + 1)/(x + 1)</math> is composite, observe that
 
+
<cmath>\begin{align*}
Let <math>{a_{n}}</math> be <math>7^{7^{n}}+1</math>. The result holds for <math>{n=0}</math> because <math>{a_0 = 2^3}</math> is the product of <math>3</math> primes.
+
\frac{x^7 + 1}{x + 1} &= \frac{(x + 1)^7 - ((x + 1)^7 - (x^7 + 1))}{x + 1} \\
 
+
&= (x + 1)^6 - \frac{7x(x^5 + 3x^4 + 5x^3 + 5x^2 + 3x + 1)}{x + 1} \\
Now we assume the result holds for <math>{n}</math>. Note that <math>{a_{n}}</math> satisfies the [[recursion]]
+
&= (x + 1)^6 - 7x(x^4 + 2x^3 + 3x^2 + 2x + 1) \\
<cmath>{a_{n+1}= (a_{n}-1)^{7}+1} = a_{n}\left(a_{n}^{6}-7(a_{n}-1)(a_{n}^{2}-a_{n}+1)^{2}\right).</cmath>
+
&= (x + 1)^6 - 7^{2m}(x^2 + x + 1)^2 \\
 
+
&= \{(x + 1)^3 - 7^m(x^2 + x + 1)\}\{(x + 1)^3 + 7^m(x^2 + x + 1)\}.
Since <math>{a_n - 1}</math> is an odd power of <math>{7}</math>, <math>{7(a_n-1)}</math> is a perfect square. Therefore <math>{a_{n}^{6}-7(a_{n}-1)(a_{n}^{2}-a_{n}+1)^{2}}</math> is a difference of squares and thus [[composite]], i.e. it is divisible by <math>{2}</math> primes. By assumption, <math>{a_n}</math> is divisible by <math>{2n + 3}</math> primes. Thus <math>{a_{n+1}}</math> is divisible by <math>{2+ (2n + 3) = 2(n+1) + 3}</math> primes as desired.
+
\end{align*}</cmath>
 
+
Also each factor exceeds 1. It suffices to check the smaller one; <math>\sqrt{7x}\leq x</math> gives
=== Solution 2 ===
+
<cmath>\begin{align*}
Notice that <math>7^{{7}^{k+1}}+1=(7+1) \frac{7^{7}+1}{7+1} \cdot \frac{7^{7^2} + 1}{7^{7^1} + 1} \cdots  \frac{7^{7^{k+1}}+1}{7^{7^{k}}+1}</math>. Therefore it suffices to show that <math>\frac{7^{7^{k+1}}+1}{7^{7^{k}}+1}</math> is composite.
+
(x + 1)^3 - 7^m(x^2 + x + 1) &= (x + 1)^3 - \sqrt{7x}(x^2 + x + 1) \\
 
+
&\geq x^3 + 3x^2 + 3x + 1 - x(x^2 + x + 1) \\
Let <math>x=7^{7^{k}}</math>. The expression becomes
+
&= 2x^2 + 2x + 1\geq 113 > 1.
<cmath>\frac{7^{7^{k+1}}+1}{7^{7^{k}}+1} = \frac{x^7 + 1}{x + 1},</cmath>
+
\end{align*}</cmath>
which is the shortened form of the [[geometric series]] <math>x^{6}-x^{5}+x^{4}-x^3 + x^2 - x+1</math>. This can be [[factor]]ed as <math>(x^{3}+3x^{2}+3x+1)^{2}-7x(x^{2}+x+1)^{2}</math>.
+
Hence <math>(x^7 + 1)/(x + 1)</math> is composite and the proof is complete.
 
 
Since <math>x</math> is an odd power of <math>7</math>, <math>7x</math> is a [[perfect square]], and so we can factor this by difference of squares. Therefore, it is composite.
 
  
 
{{alternate solutions}}
 
{{alternate solutions}}

Latest revision as of 09:47, 7 August 2014

Problem

(Titu Andreescu) Prove that for every nonnegative integer $n$, the number $7^{7^n}+1$ is the product of at least $2n+3$ (not necessarily distinct) primes.

Solutions

Solution 1

The proof is by induction. The base is provided by the $n = 0$ case, where $7^{7^0} + 1 = 7^1 + 1 = 2^3$. To prove the inductive step, it suffices to show that if $x = 7^{2m - 1}$ for some positive integer $m$ then $(x^7 + 1)/(x + 1)$ is composite. As a consequence, $x^7 + 1$ has at least two more prime factors than does $x + 1$. To confirm that $(x^7 + 1)/(x + 1)$ is composite, observe that \begin{align*} \frac{x^7 + 1}{x + 1} &= \frac{(x + 1)^7 - ((x + 1)^7 - (x^7 + 1))}{x + 1} \\ &= (x + 1)^6 - \frac{7x(x^5 + 3x^4 + 5x^3 + 5x^2 + 3x + 1)}{x + 1} \\ &= (x + 1)^6 - 7x(x^4 + 2x^3 + 3x^2 + 2x + 1) \\ &= (x + 1)^6 - 7^{2m}(x^2 + x + 1)^2 \\ &= \{(x + 1)^3 - 7^m(x^2 + x + 1)\}\{(x + 1)^3 + 7^m(x^2 + x + 1)\}. \end{align*} Also each factor exceeds 1. It suffices to check the smaller one; $\sqrt{7x}\leq x$ gives \begin{align*} (x + 1)^3 - 7^m(x^2 + x + 1) &= (x + 1)^3 - \sqrt{7x}(x^2 + x + 1) \\ &\geq x^3 + 3x^2 + 3x + 1 - x(x^2 + x + 1) \\ &= 2x^2 + 2x + 1\geq 113 > 1. \end{align*} Hence $(x^7 + 1)/(x + 1)$ is composite and the proof is complete.

Alternate solutions are always welcome. If you have a different, elegant solution to this problem, please add it to this page.

See also

  • <url>viewtopic.php?t=145849 Discussion on AoPS/MathLinks</url>
2007 USAMO (ProblemsResources)
Preceded by
Problem 4
Followed by
Problem 6
1 2 3 4 5 6
All USAMO Problems and Solutions

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png